PROJETO DE DIAGNÓSTICO DA BIBLIOTECA DO INSTITUTO DE HIGIENE E MEDICINA TROPICAL (IHMT): UM ESTUDO DE CASO DE ACERVO DOS ANAIS - Caldeira, Paulo (2018)
In this art icle, we present the diagnosis project of the Inst ituto de Higiene e Medicina Tropical (IHMT) Library and its collect ion. We selected the main tools of analysis, and the criteria and parameters proposed for the general descript ion and analysis of historical charact er of t he document s, applied in a case st udy of t he “ Anais doIHMT ”. In conclusion we point out some fut ure perspectives which may result from the proposed project .